Bioimpedance and bioelectricity basics - Grimnes, Sverre; Martinsen, rian (Academic Press, 2014)
Bioimpedance and Bioelectricity Basics, 3rd Edition paves an easier and more efficient way for people seeking basic knowledge about this discipline. This book's focus is on systems with galvanic contact with tissue, with specific detail on the geometry of the measuring system. Both authors are internationally recognized experts in the field. The highly effective, easily followed organization of the second edition has been retained, with a new discussion of state-of-the-art advances in data analysis, modelling, endogenic sources, tissue electrical properties, electrodes, instrumentation and measurements. This book provides the basic knowledge of electrochemistry, electronic engineering, physics, physiology, mathematics, and model thinking that is needed to understand this key area in biomedicine and biophysics.